A study of China-CLMV economic relations: impliciation towards CLMV countries' foreign policy / Shasha Amira Mohd Hilmi - Mohd Hilmi, Shasha Amira (2019)
Post 2007-2008 Global Financial Crisis had witnessed significant incline of CLMV s GDP and trades from previous years where commodities export for CLMV were severely impacted due to the economic slowdown of the major CLMV s trading partner. Over the years, China became the important economic partner for CLMV through high value of import and export trades, FDI, loan, technical assistance and development projects financed by China. However, there is a growing scepticism on China's interest to CLMV countries where it is observed that the economic relations influenced CLMV's foreign policy even though their economic relations are so called "no-string attached". This research aims to study the China-CLMV economic relation for the past 10 years and to what extend the economic relation have influence on CLMV countries' foreign policy. It specifically studies on the economic and politic of CLMV as important actors according to China's foreign policy driven by the geographical factor of CLMV as China's neighbour and the economic status as underdeveloped economies. This research is based on statistic obtained from multiple economic documents and interviews conducted with academician and practitioners. This research examined significant economic relations between China and CLMV due to several pull and push factors and created different level of dependency that does influence CLMV's foreign policy in certain extends especially in the South China Sea territorial dispute, One China Policy and ASEAN collectivism. This research observed that the higher the level of economic dependency that one country has with another country, the higher the capability to influence the foreign policy. Therefore, the result of the study also suggested that CLMV should lower its dependency with China's economic through several means.